Lyric lais: volume I - Buckley, Ann (Newton Abbot Antico edition)
The French lai, which flourished in the thirteenth century, is the vernacular equivalent of the Latin sequence. Lyric lais are either secular or religious; the former treat the theme of courtly love while most of the latter are devoted to the Virgin Mary. Some lyric lais survive with the monophonic melodies to which they were sung. This selection of three lais, Li Lais des Amans, Li Lais de le Rose and Li Lais du Kievrefoel, provides an excellent introductory survey of an important and attractive repertory of poetry and music nowadays almost unknown.